LEGAL ANALYSIS OF LAND ACQUISITION IN NATIONAL STRATEGIC PROJECTS: A CASE STUDY OF TOBA CASE NO. 5/PID SUS-TPK/2023/PN MDN: English - Simanjuntak, Delima Mariaigo; Syahrin, Alfi; Mulyadi, Mahmud (CV. ARGA FARMA, 2024)
This study investigates the legal considerations in a corruption case surrounding land transactions in Desa Parparean, Kecamatan Porsea, Kabupaten Toba. The defendants, Daulat Napitupulu and Lumongga Marsaulina Aruan, held land leased to PT. Dok Bahari Nusantara for ship construction. The Ministry of Transportation later selected this land for a shipyard project to enhance tourism in the Lake Toba region. Allegations of corruption emerged during the land certification and compensation processes, prompting legal proceedings. This research applies a normative juridical approach, analyzing judicial decision-making in Case No. 5/Pid.Sus-TPK/2023/PN Mdn, focusing on whether the defendants misused their authority in certifying and compensating for the land. The findings reveal complex historical and cultural dynamics, particularly around the ancestral and communal (ulayat) land rights of indigenous communities in Lake Toba. The court’s evaluation extended to regulatory inconsistencies, highlighting the need to balance environmental protection with national development interests. Although no procedural or legal violations were found in this case, the decision underscores the importance of clear legal processes in protected areas. It also validates the defendants' land ownership certificate and the compensation determined through lawful and independent appraisal. This case emphasizes the critical role of transparent judicial procedures and the protection of indigenous land rights within national strategic projects.